Characterization of a Novel 71.8 kb α0-Thalassemia Deletion and Subsequent Summary of a Practical Procedure for Thalassemia Molecular Diagnosis. (3rd July 2020) - Xu, Ming-Li; Qin, Jia-Chun; Chen, Bi-Yan; Yang, Xue-Xi; Liu, Hai-Ping; Yuan, Wei-Xi; Zhong, Jian-Mei; Huang, Li-Min; Zhou, Wan-Jun
Abstract: Thalassemia is the most common monogenic disorder around the world. Based on the principle of genotype–phenotype correlation, identification of thalassemia mutations is the essential prerequisite for clinical diagnosis and management. Because only common mutations are routinely detected, the identification of rare or undetermined mutations is a challenge for clinical laboratories. Herein, a proband presenting with inconsistent phenotype–genotype correlation after routine molecular screening was investigated by multiplex ligation-dependent probe amplification (MLPA), targeted-next generation sequencing (targeted-NGS), gap-polymerase chain reaction (gap-PCR) and Sanger sequencing. Eventually, a novel 71.8 kb deletion (– − 71.8 ) was identified and characterized, which included HBZ (ζ), HBA2 (α2), and HBA1 (α1) genes and was causing α 0 -thalassemia (α 0 -thal). Furthermore, we summarized a practical procedure based on accumulated experience in studies and clinical practice, which can be a guide for molecular screening and clinical diagnosis of thalassemia, especially for identification of undetermined or novel mutations.